Taxonomic review of the elampine cuckoo wasps from northeastern Brazil (Hymenoptera: Chrysididae), with the description of three new species - Lucena, Daercio A. A.; Santos-Neto, Pedro E.; Zanella, Fernando C. V.; Almeida, Eduardo A. B. (Zootaxa, 2022)
The diversity of the Elampini cuckoo wasps in northeastern Brazil is reviewed. Three new species are described: Hedychrum oxente Lucena & Zanella sp. nov., Holopyga lunae Lucena sp. nov., and Muesebeckidium clemensi Lucena & Zanella sp. nov. A lectotype is designated for Holopyga piliventris Ducke, 1907 and herein illustrated. Elampus aequinoctialis Ducke, 1901 is restored as a valid species (previously synonymized with Elampus gayi Spinola, 1851) and diagnosed. Holophris huberi (Ducke, 1901) and Muesebeckidium clemensi sp. nov. represent the first records of both genera to northeastern Brazil. New records along with up-to-date distributional maps are discussed, and an identification key to the species of Holopyga from northeastern Brazil is provided. The total diversity of Elampini recorded for northeastern Brazil is now represented by the following eight species: Elampus aequinoctialis Ducke, 1901, Exallopyga guatemalensis (Cameron, 1888), Hedychrum oxente Lucena & Zanella sp. nov., Holophris huberi (Ducke, 1901), Holopyga iheringi du Buysson, 1901, H. lunae Lucena sp. nov., H. piliventris Ducke, 1907, and Muesebeckidium clemensi Lucena & Zanella sp. nov.